905PDMultiple-cohort analysis investigating FGFR3 alteration as a predictor of non-response to neoadjuvant pembrolizumab (pembro) in muscle-invasive bladder cancer (MIBC). (1st October 2019) - Necchi, A; Madison, R; Chung, J; Raggi, D; Briganti, A; Montorsi, F; Boormans, J L; Liu, Y; De Jong, J J; Chung, J; Black, P C; Ross, J S; et al.
Abstract: Background: In PURE01 study (NCT02736266), neoadjuvant pembro resulted in 42% pT0 in patients (pts) with MIBC. pT0 pts had features suggesting pre-existing immunity or higher tumor mutational burden (TMB) may promote response. In this study, we investigated potential mechanisms for resistance to pembro, including FGFR3 genomic alterations (GA). Methods: Pts enrolled in the PURE-01, which is still recruiting pts in its amended design, had predominant urothelial carcinoma histology and stage cT ≤ 4N0 MIBC. Biomarker analyses in the expanded cohort of 96 pts included PD-L1 combined positive score and comprehensive genomic profiling (FoundationCDx assay). In addition, TCGA MIBC (n = 405) and a prospective commercial cohort (PCC) of 415 MIBC pts from the clinical use of the Decipher Bladder TURB test from the GRID registry (NCT02609269) were analyzed. A single-sample genomic classifier (GC) was trained to identify FGFR3-active tumors (FGFR3+). Results: In PURE01 cohort, despite a linear association of TMB with ypT0 in multivariable models (p = 0.017), there was no association between FGFR3 GA and pathological response nor with PD-L1 expression. FGFR3 GA were found in 17.6% ypT0 vs 20.7% in ypT3-4 disease (corrected p = 0.82). Applying the GC to the TCGA MIBC cohort, we found 45% of FGFR3+ cases had FGFR3 mutations vs 9% for the rest of the cohort. Applying the GC to the PCC, we found that the FGFR3+ tumors were Luminal (n = 14), Luminal Infiltrated (n = 10) or Luminal Papillary (n = 30). FGFR3+ pts showed significantly lower PD-L1 (-0.03 vs. 0.109, p < 0.001) and PD-L2 (0.184 vs. 0.389, p < 0.001), but consistent PD-1 (0.175 vs. 0.163, p = 0.48) gene expression. FGFR3+ pts had lower immune and stromal infiltration as measured by the immune190 (0.227 vs. 0.348, p < 0.001) and Estimate (100.14 vs. 1099.2, p < 0.001) gene expression signatures. Conclusions: In our combined cohorts, FGFR3 GA did not correlate with response to pembro. FGFR3 GA are enriched in FGFR3+ tumors, which in turn tend to have lower immune activity, PD-L1 and PD-L2, suggesting FGFR3 activity may provide a potential tool for further discriminating the mechanisms underlying response and resistance to neoadjuvant pembro in MIBC. Clinical trial identification: NCT02736266 (PURE01) NCT02609269 (GRID Registry). Legal entity responsible for the study: The authors. Funding: Decipher Bioscience. Disclosure: A. Necchi: Honoraria (institution), Advisory / Consultancy, Research grant / Funding (institution): Merck; Honoraria (institution), Advisory / Consultancy: Roche; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: BMS; Advisory / Consultancy, Research grant / Funding (institution): Incyte; Advisory / Consultancy: Clovis; Advisory / Consultancy: Janssen. R. Madison: Full / Part-time employment: Foundation Medicine. J. Chung: Full / Part-time employment: Foundation Medicine. Y. Liu: Full / Part-time employment: Decipher Bioscience. J. Chung: Full / Part-time employment: Foundation Medicine. J.S. Ross: Full / Part-time employment: Foundation Medicine. S.M. Ali: Full / Part-time employment: Foundation Medicine. E. Davicioni: Full / Part-time employment: Decipher Bioscience. E.A. Gibb: Full / Part-time employment: Decipher Bioscience. All other authors have declared no conflicts of interest.